Enhancing ergogenic performance and antioxidant benefits of red sugarcane juice through probiotic fermentation - Wan Mansor, Wan Nusrah; Mohd Zaini, Nurul Solehah; Gengan, Gengghatarani; Abdullah, Ariani Hoo; Mohd Sha’ari, Ainnur Adnin; Roslan, Anis Zulaikha; Abd Rahim, Muhamad Hafiz (Springer Nature, 2024)
The potential of red sugarcane as a functional probiotic drink was investigated, with a focus on determining its physicochemical, ergogenic, and antioxidant activities. Three different variants of Malaysian red sugarcane, namely Ragnar, Kapur, and Serai, were selected for analysis. The concentrations of electrolytes (Na, K, Ca, Mg, Zn, and Fe) in sugarcane juice were determined using an inductively coupled plasma mass spectrophotometer (ICP-MS), while the antioxidant activity and Vitamin C were assessed through colorimetric assays. Additionally, the functionality of the optimal variant, Ragnar, was enhanced by inoculating it with lactic acid bacteria (LAB) Lactobacillus plantarum ATCC8014 and Lactobacillus casei Shirota. High antioxidative properties (TPC: 71.63 mg GAE/mL, FRAP: 2.76 mmol TE/mL, DPPH EC50: 55.66 µg/mL, and Vitamin C: 0.72 mg/100 g) were observed in the Ragnar, which tends to exhibit an attractive blue-yellow hue. K exhibited the highest concentration in all samples (126.31 – 229.95 mg/mL), followed by Na, Mg, Fe, and Zn, which exceeded the commercial isotonic drink. The viability of LAB (above 107 CFU/mL) and the production of gamma-aminobutyric acid (GABA) were satisfactory while reducing sugars were generally lower after the fermentation. The findings present red sugarcane as a potential natural source for the development of functional drinks.